Peningkatan Aparatur Desa dalam Pelayanan Publik di Era Digital Desa Tirawuta Kecamatan Tirawuta Provensi Sulawesi Tenggara - Agusman, Yudi; Yasir, Arafat; Asrun, Laode; Alauddin, Murni Ratna Sari (Indonesian Journal of Community Services, 2023)
Digital public services in the era of the industrial revolution 4.0 is a necessity. The concept of digital public services leads to effective and efficient principles. Effective means doing something right while efficient means doing something right. Digital public services are expected to provide convenience for anyone who needs access. Digital public services are characterized by the use of media other than paper or what is often referred to as paperless. Technology has an important role so that digital public services can run as they should. Nowadays, almost everyone can run or operate a device, meaning that everyone can easily access information through the device they have. The research was carried out descriptively and interviewed related parties were to find information related to the digitization of public services. The results of the study found that currently developing technology and information such as artificial intelligence, mobile autonomy, and the internet have a very large influence on human life, especially in terms of ways of thinking and ways of behaving. Public services are currently required to be able to keep up with user requests, in this case, residents. The increasing understanding of users towards technology has an impact on the user's desire to get services that are practical, economical, fast, and precise. Digital public services are one of the solutions to address these challenges.